Atmospheric Corrosion, Antibacterial Properties, and Toxicity of Silver Nanoparticles Synthesized by Two Different Routes - I. DeAlba-Montero; Claudio A. Ruiz-Torres; Diana P. Portales-Pérez; Fidel Martínez-Gutierrez; Félix Echeverría; Martha E. Compeán-Jasso; Yolanda G. Cataño-Cañizales; Facundo Ruiz (Bioinorganic Chemistry and Applications)
Silver nanoparticles (AgNPs) have been widely employed or incorporated into different materials in biological application, due to their antibacterial properties. Therefore, antimicrobial capacity and cytotoxicity have been highly studied. However, most of these reports do not consider the possible corrosion of the nanomaterials during their exposure to atmospheric conditions since AgNPs undergo a transformation when they come in contact with a particular environment. Derived from this, the functionality and properties of the nanoparticles could decrease noticeably. The most common silver corrosion process occurs by the interaction of AgNPs with sulfur species (H2S) present in the atmospheric air, forming a corrosion layer of silver sulfide around the AgNPs, thus inhibiting the release of the ions responsible for the antimicrobial activity. In this work, AgNPs were synthesized using two different methods: one of them was based on a plant extract (Brickellia cavanillesii), and the other one is the well-known method using sodium borohydride (NaBH4). Chemical stability, corrosion, antibacterial activity, and toxic activity were evaluated for both sets of prepared samples, before and after exposition to atmospheric air for three months. The structural characterization of the samples, in terms of crystallinity, chemical composition, and morphology, evidenced the formation of link structures with nanobridges of Ag2S for non- “green” AgNPs after the air exposition and the intact preservation of silver core for the “green” sample. The antibacterial activity showed a clear improvement in the antimicrobial properties of silver in relation to the “green” functionalization, particle size control, and size reduction, as well as the preservation of the properties after air exposition by the effective “green” protection. The cytotoxicity effect of the different AgNPs against mononuclear cells showed a notable increment in the cell viability by the “green” functionalization.